Innovative Solidarities in Europe’s Sustainability Transitions: A Mechanism-Based Account - Bazzani, Giacomo (Zeitschrift für Theoretische Soziologie, 2026)
Across Europe, practices such as climate mutual aid, community energy cooperatives, refugee support networks, and just transition alliances signal a reconfiguration of solidarity under ecological crisis. Building on recent work on altruistic solidarity, we conceptualize solidarity as patterned prosocial practice and use ›innovative solidarity‹ as a flexible label for heterogeneous forms that reach beyond bounded identities and reciprocity. Developing a mechanism-based framework, we specify how shared ethical commitments, recognition of interdependence, and deliberate cooperation across difference generate solidarities that operate across translocal, transnational, and cross-generational scales. To illustrate the framework, we draw on four well-documented European cases – youth climate strikes, community energy cooperatives, just transition coalitions, and disaster mutual aid networks – to show how these mechanisms are enacted, stabilized, and sometimes undermined in practice. The case illustrations suggest how innovative solidarities can support sustainability transitions by expanding who is included in the ›we‹ of solidarity to distant others and future generations.